SATIR ON THE POLITICAL MEME OF PRESIDENT DONALD TRUMP: A SEMANTIC - Brigitta Vidya Salsabila; Ervina CM Simatupang (English Journal Literacy Utama, 2021)
The title of this research is “ Satir Pada Meme Politik Presiden Donald Trump : Kajian Semantis.” This study aims to identify types of satire and the elements of satire in meme of Presiden Donald Trump which contain critism. The method used in this study is the Descriptive Analysys method, which is method is collect the data then processed and analyzing the data and drawing the conclusion. Theory of satire used in this study is based on Abraham (2013 : 175) and Griffin (1994: 1). Theory of types of satire is based on Quintero (2007: 104) theory and the element of satire used Robert Harris (2004) theory. The result of this research from 30 data, there is 2 types of satire, that is Horatian Satire found consist 16 (53,3%) data and Juvenalian Found consist 14 (46,7%) data. Based types of satire, is consist of elements of satire. From Horatatian satire is consist element of Sarcasm 5 data (16,7%), Irony 4 data (13,3%), Hyperbole 2 data (6,6%), and Parody 5 data (16,7%). From Juvenalian satire, is consist element of Sarcasm 7 data (23,4%), Irony 5 data (16,7%), and Hyperbole 2 data (6,6%). The conclusion of this research is the Horatian satire are mostly found, that is 16 data and the Sarcasm is mostly found in the element of satire, that is 12 data.